GMO authorisations and the Aarhus Regulation: Paving the way for precautionary GMO governance?. Issue 4 (August 2019) - Leonelli, Giulia Claudia
This article endeavours to assess whether existing case law under the Aarhus Regulation has opened up any opportunities for civil society to challenge the decision that, in the face of scientific uncertainty, genetically modified organism risks meet the intended European Union levels of health and environmental protection. Against this backdrop, it seeks to establish whether the actions of non-governmental organizations under the Aarhus Regulation have resulted in any meaningful review of the Commission's exercise of its discretion, in accordance with the overarching tenets of the precautionary principle and the aim of a high level of health and environmental protection. Upon an in-depth analysis of the recent TestBioTech cases, the article puts forward an argument for different evidentiary rules and a different standard of review in Aarhus Regulation case law, advocating a clearer distinction between 'standard' action for annulment and annulment of a decision to reject a request for internal review. This is argued to be the only way forward to breathe some life into the Aarhus Regulation's provisions, ensuring some scrutiny of the level of protection achieved and nudging the Commission to take the precautionary principle seriously in the genetically modified organism field.